Comparing patient satisfaction and intubating conditions using succinylcholine or low-dose rocuronium for rigid bronchoscopy: a randomized study - Ghezel-Ahmadi, Verena; Beck, Grietje (The thoracic and cardiovascular surgeon, 2015)
Introduction: Despite its serious side effects, succinylcholine is commonly used for neuromuscular relaxation in short procedures, such as rigid bronchoscopy and tracheobronchial interventions. The application of low-dose rocuronium reversed by low-dose sugammadex might be a modern alternative. The aim of this study was to compare patient satisfaction, incidence of postoperative myalgia (POM) as well as intubating conditions of these two muscle relaxants for rigid bronchoscopy.
Gesehen am 03.12.2018
21.November 2014 (eFirst)